1999
DOI: 10.1038/sj.mp.4000466
|View full text |Cite
|
Sign up to set email alerts
|

Neuroticism is not associated with the serotonin transporter (5-HTTLPR) polymorphism

Abstract: A deletion/insertion polymorphism in the transcriptional control region of the serotonin transporter gene (5-HTTLPR) was reported to be associated with dimensional measures of neuroticism, 1 although subsequent replication attempts have failed.2-5 These replication attempts, however, have been dissimilar to the initial study in sample size, distribution of allelic frequency and/or assessment of neuroticism. The current study was conducted in a further attempt to replicate the initial finding using: (a) a sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
61
5
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(72 citation statements)
references
References 25 publications
5
61
5
1
Order By: Relevance
“…SERPR long and short allele frequencies were, respectively, 0.51 and 0.49, similar to those of previously published samples in Caucasians 45,59,69,70 and similar to those observed in our Italian sample (0.57 and 0.43, respectively). 60 Italian and Greek samples were not different in terms of SERTPR genotypes frequencies (w 2 ¼ 4.3; df ¼ 2; P ¼ 0.1).…”
Section: Resultssupporting
confidence: 91%
“…SERPR long and short allele frequencies were, respectively, 0.51 and 0.49, similar to those of previously published samples in Caucasians 45,59,69,70 and similar to those observed in our Italian sample (0.57 and 0.43, respectively). 60 Italian and Greek samples were not different in terms of SERTPR genotypes frequencies (w 2 ¼ 4.3; df ¼ 2; P ¼ 0.1).…”
Section: Resultssupporting
confidence: 91%
“…4 However, the association with personality has not been supported in subsequent studies. 9,10 Although we did not find evidence for a main effect of 5-HTTLPR on smoking status in a previous analysis, 11 Hu and colleagues 12 have provided evidence that the 5-HTTLPR modifies the association of neuroticism with smoking status. In the present report, we sought to replicate and extend the findings by Hu et al 12 examining the interacting effects of the 5-HTTLPR and neuroticism on smoking practices and nicotine dependence in an independent sample of smokers.…”
mentioning
confidence: 55%
“…11 In possible support of this idea, a United States study 12 found a significant interaction between 5-HTTLPR genotype and race for NEO-PI-R neuroticism, which suggests that the relationship between the allele and anxiety-related traits may be obscured by the effects of differing phenotypes and differing gene frequencies in different populations (population stratification). Several other studies [13][14][15] found no association of the 5-HTTLPR with various personality measures. Unfortunately, none of the negative studies included family material, which is essential to distinguish genuine genetic transmission, or its lack, from artifacts of population stratification.…”
mentioning
confidence: 87%